PEMANFAATAN CERITA RAKYAT NABIRE UNTUK MENINGKATKAN MINAT BACA MURID SEKOLAH DASAR - Selestinus Dialis; Wigati Yektiningtyas; Yan Dirk Wabiser (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
This study aims to analyze the use of Nabire folktales as Indonesian language learning media to increase reading interest in fifth-grade students at SDN Inpres 01 Bumiraya Nabire, Central Papua. The research was motivated by students' low reading interest, as evidenced by their lack of involvement in reading activities, low library visits, and limited reading comprehension skills. Folktales were chosen because they contain cultural and moral values ​​that are close to students' lives, thus increasing their involvement in literacy activities. The study used a descriptive qualitative approach with a case study design. The research subjects consisted of fifth-grade teachers and students selected through purposive sampling techniques. Data were collected through observation, semi-structured interviews, and documentation. Data analysis used the Miles and Huberman interactive model, which includes data reduction, data presentation, conclusion drawing and verification. Data validity was tested through triangulation of sources and techniques. The results showed that the use of Nabire folktales in Indonesian language learning was able to increase students' reading interest. Reading materials became more interesting, relevant to students' cultural experiences, and encouraged active participation in reading activities and discussions. In addition, the use of folktales helped students understand local moral and cultural values ​​and improved reading literacy skills. Thus, Nabire folk tales are effectively used as contextual learning media in elementary schools.